Good governing: the police power in the American states - Rodriguez, Daniel B. (Cambridge University Press, 2024)
"Drawing upon law, history, and social science, this book is a close investigation of an important yet neglected area of constitutional law: the state police power and its function in regulatory governance in the U.S. It is a major contribution to state constitutional law literature and contemporary regulatory policy"-- Provided by publisher